Pengembangan Lembar Kerja Siswa Berbasis Karakter Terhadap Kemampuan Berpikir Kritis Siswa - Etthy Christin Christin (LPD IKIP PGRI Pontianak, 2022)
The purpose of this study was to develop a valid, practical, and effective character-based student worksheet learning media for critical thinking skills on the Pythagorean theorem material in class VIII SMP Negeri 3 Banyuke Hulu. The method used is a research and development method with a 4D research design which is limited to only Define, Design, and Develop. The subjects in this study were 28 students of class VIII SMP. 3 material experts and media experts. The instruments used in this study were material expert validation sheets and media expert validation sheets, teacher response questionnaires, student response questionnaires, and critical thinking ability test questions. Based on the results of the research that has been carried out, the results of the validation of the character-based Student Worksheet learning media (LKS) have an average level of validity of 85.85% with very valid criteria, the practicality level of the Student Worksheet learning media (LKS) is 93.5% with very practical criteria, and the level of effectiveness of the Student Worksheet (LKS) learning media is 82.14% with very effective criteria.